Melatonin-Induced Inhibiton of Spontaneous and Oxytocin-Induced Contractions in Isolated Human Myometrium - Tuğ, Niyazi; Ayar, Ahmet (Fırat University, 2001)
Aim: The aim of this study was to investigate the effects of melatonin on spontaneous and oxytocin-induced contractility of myometrim isolated from pregnant women. Material and Methods: Myometrial strips were removed from pregnant women undergoing elective sezarien section and placed in an organ bath containing Lehrer solution at 37°C and pH 7.4, constantly bubbled with 95% oxygen-5% carbon dioxide and isometric contractions were recorded. Effects of cumulative concentrations of melatonin (1-25µ M) on amplitude and frequency of spontaneous and oxytocin-induced contractions were studied. Statistical analysis was performed using Kruskal Wallis analysis of variance. Results: Melatonin inhibited amplitude and frequency of both spontaneous and oxytocin-induced contractions of myometrium in a dose-dependent manner. Conclusions: Data from this study indicate that melatonin inhibits spontaneous and oxytocin-induced contractions in of myometrium isolated pregnant woman.

Amaç: Bu çalışmanın amacı izole gebe insan miyometriyumunda spontan ve oksitosinle indüklenen kontraksiyonlara melatoninin etkilerini inçelemektir. Gereç ve Yöntem: Sezeryan operasyonu esnasında alınan miyometriyum kesitleri içerisinde 37°C (pH 7.4) Lehrer solüsyonu bulunan ve %95 O2-%5 CO2 gaz karışımı ile sürekli gazlandırılan izole organ banyosuna asılarak izometrik kontraksiyonlar kayıt edildi. Melatoninin kümülatif olarak uygulanan (1-25µ M) dozlarının spontan ve oksitosinle indüklenen kontraksiyonların amplitüt ve frekansları üzerine etkisi incelendi. İstatistiksel değerlendirmede Kruskal Wallis varyans analizi kullanıldı. Bulgular: Melatonin spontan ve oksitosinle indüklenen kontraksiyonların hem amplitüt hem de frekanslarını doz bağımlı olarak inhibe etti. Sonuç: Bu çalışmanın sonuçları melatoninin izole gebe insan miyometriyumunda spontan ve oksitosinle indüklenen kontraksiyonları inhibe ettiğini göstermektedir.
İZOLE İNSAN MİYOMETRİYUMUNDA SPONTAN VE OKSİTOSİNLE İNDÜKLENEN KONTRAKSİYONLARIN MELATONİNLE İNHİBİSYONU